One enhancer mediates mafK transcriptional activation in both hematopoietic and cardiac muscle cells - Katsuoka, Fumiki (Oxford University Press, 2000)
Members of the small Maf family of transcription factors play important roles in hematopoiesis. Using transgenic assays, we discovered a tissue-specific enhancer 3′ to the mafK gene. This enhancer directs mafK transcription in hematopoietic as well as in developing cardiac muscle cells, and was thus designated the hematopoietic and cardiac enhancer of mafK (HCEK). Only two of four GATA consensus motifs identified within HCEK contributed to enhancer activity, and both of these sites were required for both cardiac and hematopoietic transcriptional activation. The expression profile of MafK significantly overlapped that of GATA-1 in hematopoietic cells and of GATA-4/-6 in cardiac tissues. Each of these GATA factors bound with high specificity to both of the critical GATA sites in HCEK. Hence, the mafK gene is regulated by different GATA proteins in the hematopoietic and cardiac compartments through the same two GATA-binding sites in HCEK. These data provide the first in vivo demonstration that distinct members of a related transcription factor family activate the tissue-specific expression of a single target gene using the same cis-regulatory element.